Proposta de sistematização para a etapa conceitual do processo de desenvolvimento de produto no segmento têxtil - Rodrigues, Ronaldo dos Santos (2012)
The Brazilian textile industry is the fifth largest producer in the world. However, it has an inefficient product development process (PDP), not employing formal design methodologies, since some of them are already well established in the industrial segment. Specifically in the development of knitted fabric, the experience of the technical developer is fundamental, but it does not avoid reworking, which is most of the time guided by a trial and error approach, causing delays in the collections launching. Data from a field survey suggest that the conceptual design phase, for example, is one of the most neglected. The classical methodologies for PDP indicate that the stage of conceptual design is important because it focuses, among other things, on the cost and product differentiation. The references concerning the textile PDP emphasize the conceptual design is related to the product success. However, this literature does not indicate how to implement the conceptual design in the textile environment. This dissertation proposes the development of a model and a tool for implementing conceptual phase for knitted products. First, it started with the research of some classic methodologies of PDP, the textile industry and its segments and the PDP in the textile industry. After that, the survey was conducted with companies working with knitted products in order to diagnose their PDPs. Then, the results were compared to bibliographical references in order to identify gaps in those practices. Based on the analysis that the conceptual phase is the most critical in practice, a methodology for the development of the conceptual phase was devised, based on Back and co-authors. Subsequently, a computational tool was implemented in order to generate records during all process. To validate the tool, the experiment was conducted simulating design situations. Finally, the participants answered a questionnaire regarding the model and tool performances. The results were positive, indicating that these model and tool are relevant for the development of knitted fabric, increasing assertiveness in its development.